2009
DOI: 10.1111/j.1524-4741.2009.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Subtypes as Defined by the Estrogen Receptor (ER), Progesterone Receptor (PR), and the Human Epidermal Growth Factor Receptor 2 (HER2) among Women with Invasive Breast Cancer in California, 1999-2004

Abstract: Breast cancer research examining either molecular profiles or biomarker subtypes has focused on the estrogen receptor negative/progesterone receptor negative/human epidermal growth factor receptor 2 negative (ER-/PR-/HER2-) and ER-/PR-/HER2+ subtypes. Less is known about the epidemiology or clinical outcome of the other subtypes. This study examines the eight combinations of ER/PR/HER2 in patients with invasive breast cancer. The 5-year relative survival and the distribution among demographic, socioeconomic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
229
5
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(259 citation statements)
references
References 46 publications
20
229
5
5
Order By: Relevance
“…Luminal A subtype, which comprised 62.1% of the current cohort, had a best survival compared with other subtypes, this finding is consistent with most previous studies [4,5,7,8] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Luminal A subtype, which comprised 62.1% of the current cohort, had a best survival compared with other subtypes, this finding is consistent with most previous studies [4,5,7,8] .…”
Section: Discussionsupporting
confidence: 81%
“…Many researchers therefore 1111  classified breast cancer patients into four subtypes based on the expression of ER, PR and HER2: luminal A (ER+ and/or PR+, HER2-); luminal B (ER+ and/or PR+, HER2+); HER2+ subtype (ER-, PR-, HER2+) and triple-negative subtype (ER-, PR-, HER2-). Previous studies suggested that patients with luminal A have a favorable prognosis when compared with patients with luminal B, HER2+ or triple-negative subtype [4,7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…3,9,24 Our previous research revealed that women with triple-negative breast cancer were significantly more likely to be African American or Hispanic and live in socioeconomically deprived areas, 14,15 and age was found to have an important role in determining the ER/PR/HER2 subtype. 16,17 Although racial disparities in breast cancer treatment and outcomes have been previously well documented, 3,[25][26][27] the interplay between race/ethnicity and SES and their respective causative effect on breast cancer outcomes remain controversial. 28 Furthermore, it remains difficult to completely unravel the intertwining aspects of these factors in addition to tumor biology and age.…”
Section: Discussionmentioning
confidence: 99%
“…The details of documentation of estrogen receptor (ER) progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) in breast cancer along with age and stage at diagnosis, tumor grade, tumor subtype, race/ethnicity, and socioeconomic status (SES) have been extensively described in our previous publications [14][15][16]21 and by the California Cancer Registry. 20 RT Radiation treatment was recorded in the cancer registry for all documented cancer-directed RT performed as the first course of treatment.…”
Section: Case Identificationmentioning
confidence: 99%
See 1 more Smart Citation